Sintered body
By adding stabilizing elements and dispersed metal oxides to the zirconia sintered body, the problem of increasing hardness and deterioration of processability when increasing the light shielding properties of the zirconia sintered body is solved, and high light shielding properties and excellent processability are achieved.
Patent Information
- Application Number
- CN202380069746.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-09-28
- Publication Date
- 2025-05-09
AI Technical Summary
When the existing zirconia sintered body increases light shielding properties, the hardness is improved and the processability is deteriorated, making it difficult to take into account both.
By adding zirconia containing stabilization elements to the zirconia sintered body, the stabilization element content is ensured to have a specific peak in the XRD pattern, combining dispersed phase metal oxides to improve light shielding and processability.
It realizes high light shielding and excellent processability of zirconia sintered bodies, reduces Vickers hardness and reduces total light transmittance, and is suitable for a variety of applications.
Smart Images

Figure BDA0005334100290000221 
Figure BDA0005334100290000231
Abstract
Description
Technical Field
[0001] The present invention relates to a sintered body, and in particular to a sintered body mainly containing zirconium oxide, which has high light-shielding properties and high processability. Background Art
[0002] Regarding sintered bodies based on zirconium oxide, in addition to existing uses that require strength, such as pulverized media and structural materials, applications in decorative uses such as decorative parts for watches, portable electronic devices, automobiles, and home appliances are also being studied. Sintered bodies used for decorative purposes require high strength and high toughness in order to prevent fractures caused by external impacts. So far, various sintered bodies with high strength and high toughness have been reported as highly reliable materials.
[0003] In Patent Document 1, a sintered body is reported, which is formed by including a tetragonal zirconia composite powder and a TiO2 nanopowder, wherein the tetragonal zirconia composite powder contains 79.8 to 92 mol% of ZrO2 and 4.5 to 10.2 mol% of Y2O3, and 3.5 to 7.5 mol% of Nb2O5 or 5.5 to 10.0 mol% of Ta2O5, and the mass ratio of the TiO2 nanopowder to the zirconia composite powder exceeds 0 mass% and is 2.5 mass% or less. It is reported that the sintered body can reduce the hardness of zirconia while maintaining high strength and high toughness, and thus can provide zirconia with excellent processability. The zirconia sintered body of Patent Document 1 is a translucent zirconia sintered body with translucency.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-127294 Summary of the invention
[0007] Technical problem to be solved by the invention
[0008] In recent years, from the perspective of aesthetics as an exterior member, it is desired that zirconia sintered bodies have light-shielding properties. Generally, it is known that light-shielding properties can be obtained by adding alumina to zirconia sintered bodies in a normal pressure and normal temperature sintering process. However, as the amount of alumina added increases, the hardness of the zirconia sintered body increases and the processability deteriorates.
[0009] An object of the present invention is to provide a sintered body of zirconium oxide having both good processability and light-shielding properties.
[0010] Technical solutions for solving technical problems
[0011] That is, the present invention is as described in the claims, and the gist of the present invention is as follows.
[0012] [1] A sintered body comprising zirconium oxide containing a stabilizing element, wherein the content of the stabilizing element is less than 3.0 mol %, and wherein the sintered body has a peak at 2θ=34.0°±0.2° in an XRD spectrum.
[0013] [2] The sintered body according to [1], wherein the stabilizing element includes at least one selected from yttrium, gadolinium, ytterbium, and erbium.
[0014] [3] The sintered body according to [1] or [2], wherein the stabilizing element includes yttrium and at least one selected from gadolinium, ytterbium, and erbium.
[0015] [4] The sintered body according to any one of [1] to [3], wherein the ratio of the intensity at 2θ=30.0°±0.2° to the intensity of the peak top at 2θ=34.0°±0.2° in the XRD spectrum is 10 or more and 1000 or less.
[0016] [5] The sintered body according to any one of [1] to [4], comprising at least one selected from the group consisting of magnesium, calcium, strontium, barium, lanthanum, neodymium and samarium, and aluminum.
[0017] [6] The sintered body according to any one of [1] to [5], having a Vickers hardness of 12.3 GPa or less.
[0018] [7] The sintered body according to any one of [1] to [6], wherein the total light transmittance is 20% or less.
[0019] [8] The sintered body according to any one of [1] to [7], wherein the measured density is 5.4 g / cm 3 Above and 6.3g / cm 3 the following.
[0020] [9] The sintered body according to any one of [1] to [8], comprising zirconium oxide grains and dispersed phase grains, wherein the average grain size of the zirconium oxide grains is smaller than the average grain size of the dispersed phase grains.
[0021]
[10] The sintered body according to any one of [1] to [9], comprising grains of a dispersed phase, wherein the average aspect ratio of the grains of the dispersed phase is 1.5 to 3.5. DETAILED DESCRIPTION
[0022] Hereinafter, the sintered body of the present invention will be described with reference to the examples of the embodiments. It should be noted that the respective compositions and parameters disclosed in this specification can be arbitrarily combined, and the upper and lower limits of the values disclosed in this specification can be arbitrarily combined.
[0023] The sintered body of the present embodiment includes zirconium oxide containing a stabilizing element, wherein the content of the stabilizing element is less than 3.0 mol %, and the sintered body has a peak at 2θ=34.0°±0.2° in an XRD spectrum.
[0024] The zirconium oxide contained in the sintered body of the present embodiment contains a stabilizing element. That is, it contains a stabilizing element of more than 0 mol%. The stabilizing element is an element that stabilizes the zirconium oxide, and examples thereof include rare earth elements. In the zirconium oxide contained in the sintered body of the present embodiment, as a stabilizing element, it is preferred to include at least one selected from the group consisting of yttrium (Y), gadolinium (Gd), ytterbium (Yb) and erbium (Er), more preferably at least one selected from the group consisting of yttrium, gadolinium and ytterbium, and further preferably yttrium and gadolinium. From the perspective of high strength of the sintered body, the rare earth element preferably includes yttrium. From the perspective of ease of sintering with a smaller amount of stabilizing elements, the rare earth element preferably includes gadolinium. In order to easily improve the hydrothermal degradation resistance of the sintered body, the rare earth element preferably includes ytterbium. The zirconium oxide contained in the sintered body of the present embodiment may include two or more of the above-mentioned rare earth elements. The zirconium oxide contained in the sintered body of the present embodiment preferably contains yttrium and at least one selected from the group consisting of gadolinium (Gd), ytterbium (Yb) and erbium (Er). For example, the zirconium oxide contained in the sintered body of the present embodiment preferably contains yttrium and gadolinium. Thus, a sintered body having high strength and being easy to sinter with a small amount of stabilizing elements can be obtained.
[0025] The content of the stabilizing element (hereinafter also referred to as "stabilizing element amount") is sufficient as long as the zirconium oxide can be partially stabilized. The stabilizing element amount is the total content of one or more stabilizing elements contained in the sintered body, and may be more than 0 mol%, more than 1.0 mol%, or more than 1.4 mol%, and may be less than 3.0 mol%, less than 2.9 mol%, or less than 2.8 mol%. It is more preferably more than 0 mol% and less than 3.0 mol%, more than 0 mol% and less than 2.9 mol%, and more preferably more than 1.4 mol% and less than 2.8 mol%. In the present embodiment, the stabilizing element amount is the ratio (mol%) of the total amount of the stabilizing element after oxide conversion to the total amount of the stabilizing element after oxide conversion of zirconium oxide and the stabilizing element. For example, the amount of stabilizing elements in a sintered body containing zirconium oxide containing ytterbium and yttrium (ytterbium-yttrium-stabilized zirconia sintered body) can be calculated by {(Yb2O3+Y2O3) / (Yb2O3+Y2O3+ZrO2)}×100 (mol%).
[0026] The oxide conversion of the stabilizing element may be, for example, Yttrium as Y2O3, gadolinium as Gd2O3, ytterbium as Yb2O3, and erbium as Er2O3.
[0027] As long as the sintered body of the present embodiment satisfies the above-mentioned stabilizing element amount, the content of various stabilizing elements (hereinafter, the content of various stabilizing elements in the case where the stabilizing element is ytterbium, etc., respectively, is also referred to as "ytterbium content", etc.) can be arbitrary. As the content of various stabilizing elements in the sintered body of the present embodiment, the ytterbium content, the gadolinium content, and the erbium content can be respectively more than 0 mol%, more than 1.0 mol%, or more than 1.4 mol%, and can also be less than 3.0 mol% or less than 2.0 mol%. Further examples include more than 0 mol% and less than 3.0 mol%, more than 1.0 mol% and less than 3.0 mol%, or more than 1.4 mol% and less than 2.0 mol%. For example, the yttrium content can be more than 0.1 mol% or more than 0.2 mol%, less than 3.0 mol% or less than 2.0 mol%, and can further include more than 0.1 mol% and less than 3.0 mol%, or more than 0.2 mol% and less than 2.0 mol%.
[0028] The content of each stabilizing element in the present embodiment is the ratio (mol %) of each stabilizing element in terms of oxide relative to the total amount of zirconium oxide and the stabilizing element in terms of oxide.
[0029] The sintered body of the present embodiment may contain a coloring component. Thus, the sintered body presents a color tone different from the original color tone of zirconium oxide. The coloring component contained in the sintered body of the present embodiment is an element other than a rare earth element that has the function of coloring zirconium oxide, for example, preferably a metal element, and more preferably a transition metal element. As a specific coloring component, it is more preferably one or more selected from the group consisting of titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu) and zinc (Zn), and more preferably one or more selected from the group consisting of iron, cobalt and zinc.
[0030] The coloring component contained in the sintered body of the present embodiment may be in any form, but the coloring component is preferably contained in the form of a metal oxide having a perovskite structure or a spinel structure, and more preferably contained in the form of a transition metal oxide having a perovskite structure or a spinel structure.
[0031] Metal oxides having a perovskite structure include oxides represented by ABO3, wherein A is one or more selected from the group consisting of calcium (Ca), strontium (Sr), barium (Ba) and bismuth (Bi), and B is one or more selected from the group consisting of vanadium, chromium, manganese, iron, cobalt, nickel and aluminum (Al).
[0032] The metal oxide having a spinel structure may be an oxide represented by AB2O4, wherein A and B are respectively one or more selected from the group consisting of calcium, strontium, barium, bismuth, vanadium, chromium, manganese, iron, cobalt, nickel and aluminum, and preferably an oxide represented by AB2O4. Specific examples of the metal oxide having a spinel structure include CoAl2O4, Fe3O4 and Mn3O4 (i.e., Fe 2+ Fe 3+ 2O4 and Mn 2+ Mn 3+ 2O4), preferably at least one of CoAl2O4 and Mn3O4.
[0033] From the viewpoint that sinterability becomes better, the less the content of coloring component in the sintered body of the present embodiment, the more preferred. The content of coloring component exceeds 0 mass %, preferably more than 0.001 mass %. As the upper limit of the content of coloring component, for example, 5 mass %, 3.0 mass %, less than 3.0 mass %, 2.5 mass %, 2.0 mass %, 1.5 mass %, 1.0 mass % or 0.7 mass % can be cited. Further, more than 0 mass % and 5 mass %, more than 0 mass % and 3.0 mass %, more than 0 mass % and 2.5 mass %, more than 0.001 mass % and 2.0 mass %, more than 0.001 mass % and 1.5 mass % or less, more than 0.001 mass % and 1.0 mass % or more than 0.001 mass % and 0.7 mass % or less can be cited. The content of coloring component can be obtained as the ratio of the total mass of the coloring component after oxide conversion relative to the mass of the sintered body after oxide conversion. Regarding the oxide conversion of the coloring components, for example, cobalt may be represented by Co 3 O 4 , iron may be represented by Fe 2 O 3 , manganese may be represented by MnO 2 , and zinc may be represented by ZnO.
[0034] The sintered body of the present embodiment preferably contains a dispersed phase. The term "containing a dispersed phase" refers to a hexaaluminate containing at least one metal element selected from the group consisting of magnesium, calcium, strontium, barium, lanthanum, neodymium, and samarium (hereinafter, also referred to as "hexaaluminate raw material metal element" or "dispersed phase metal element"), and may also contain an aluminate of a dispersed phase metal element. The sintered body of the present embodiment has a dispersed phase, so that the total light transmittance is reduced, the light shielding property is improved, the hardness is reduced, and the processability is improved.
[0035] Hereinafter, the hexaaluminate of a dispersed-phase metal element may be simply referred to as “hexaaluminate”, and the aluminate of a dispersed-phase metal element may be simply referred to as “aluminate”.
[0036] The sintered body of the present embodiment preferably contains a dispersed phase metal element and an aluminum metal element. The content of the dispersed phase metal element is sufficient as long as at least an amount of hexaaluminate can be obtained. The content of the dispersed phase metal element (hereinafter, the content of the dispersed phase metal element in the case where the dispersed phase metal element is magnesium, etc., is also referred to as "magnesium content", etc.) can be, for example, 0.001 mass% or more or 0.005 mass% or more, and can also be 15 mass% or less or 10 mass% or less, and further can be 0.001 mass% or more and 15 mass% or less, or 0.005 mass% or more and 10 mass% or less.
[0037] In particular, the magnesium content may be, for example, 0.00618 mass % or more, 1.85 mass % or less, or 1.24 mass % or less, and further 0.00618 mass % or more and 1.85 mass % or less, or 0.0618 mass % or more and 1.24 mass % or less; the calcium content may be 0.00840 mass % or more, 2.52 mass % or less, or 1.68 mass % or less, and further 0.00840 mass % or more. % and 2.52% by mass, or 0.0618% and 1.68% by mass; the strontium content may be 0.0145% or more by mass, or 0.145% or more by mass, or 4.35% or less by mass, or 0.145% or more by mass and 2.90% or less by mass; the barium content may be 0.0200% or more by mass, or 0.200% or more by mass, or 6.00% or less by mass, or 4.35% or less by mass, or 0.145% or more by mass and 2.90% or less by mass; .00 mass % or less, further 0.0200 mass % or more and 6.00 mass % or less, or 0.200 mass % or more and 4.00 mass % or less; lanthanum content can be 0.0255 mass % or more, further 6.75 mass % or less or 4.50 mass % or less, further 0.0255 mass % or more and 6.75 mass % or less, or 0.255 mass % or more and 4.50 mass % or less; neodymium content can be 0.0231 mass % or more or 0.23 The samarium content can be 0.0237% by mass or more, and can also be 7.11% by mass or less or 4.74% by mass, and can further be 0.0237% by mass or more and 7.11% by mass or less or 0.237% by mass or more and 4.74% by mass or less.
[0038] The content of the dispersed phase metal element can be obtained as the ratio of the total mass of the dispersed phase metal element after oxide conversion to the mass of the sintered body after oxide conversion. Regarding the oxide of the dispersed phase metal element after oxide conversion, magnesium is MgO, calcium is CaO, strontium is SrO, barium is BaO, lanthanum is La2O3, neodymium is Nd2O3, and samarium is Sm2O3.
[0039] The aluminum content can be, for example, 0.0763 mass % or more or 0.763 mass % or more, and can also be 28.1 mass % or less or 18.8 mass % or less, and can further be 0.0763 mass % or more and 28.1 mass % or more and 18.8 mass % or less. The aluminum content can be obtained as the ratio of the total mass of aluminum converted to oxide to the mass of the sintered body converted to oxide. The aluminum converted to oxide can be set to Al2O3.
[0040] The sintered body of the present embodiment preferably contains at least a dispersed phase metal element and an aluminum element in the form of a hexaaluminate. Here, aluminate refers to an aluminum-containing compound having a perovskite structure and belonging to a cubic system, and hexaaluminate refers to an aluminum-containing compound having a layered structure and belonging to a hexagonal system. Examples of the layered structure include a β-alumina structure and a magnetoplumbite structure. For example, in the sintered body of the present embodiment, as the hexaaluminate, an aluminum-containing compound selected from the group consisting of MgAl 12 O 19 , CaAl 12 O 19 、SrAl 12 O 19 , BaAl 12 O 19 、LaAl 11 O 18 、NdAl 11 O 18 and SmAl 11 O 18 At least one of the group consisting of, preferably comprising MgAl 12 O 19 , CaAl 12 O 19 、SrAl 12 O 19 , BaAl 12 O 19 、LaAl 11 O 18 At least one of, and selected from CaAl 12 O 19 、SrAl 12 O 19 、LaAl11 O 18 At least one of .
[0041] The sintered body of this embodiment may contain a dispersed phase metal element and an aluminum element in the form of a compound other than hexaaluminate in addition to the hexaaluminate. Examples of the compound other than the hexaaluminate include magnesium aluminate, calcium aluminate, strontium aluminate, barium aluminate, lanthanum aluminate, neodymium aluminate, and samarium aluminate.
[0042] The mass ratio of the hexaaluminate to the sintered body of the present embodiment (hereinafter also referred to as "hexaaluminate content") is preferably 1 mass% or more. The hexaaluminate content is more preferably 3 mass% or more or 5 mass% or more. In addition, the hexaaluminate content is preferably 25 mass% or less or 20 mass% or less, and further preferably 3 mass% or more and 25 mass% or less, or 5 mass% or more and 20 mass% or less.
[0043] The mass ratio of the hexaaluminate in this embodiment is the ratio of the total mass of the hexaaluminate to the mass of the sintered body in terms of oxide. 12 O 19 , CaAl 12 O 19 、SrAl 12 O 19 , BaAl 12 O 19 、LaAl 11 O 18 、NdAl 11 O 18 and SmAl 11 O 18 Just calculate it.
[0044] The sintered body of the present embodiment includes zirconium oxide containing a stabilizing element, and is preferably a sintered body with zirconium oxide containing a stabilizing element as a matrix (parent material), i.e., a so-called zirconium oxide sintered body, or a partially stabilized zirconium oxide sintered body. The mass ratio of zirconium oxide containing a stabilizing element in the sintered body of the present embodiment (hereinafter, also referred to as "zirconia content") is preferably 65% by mass or more, 70% by mass or more, more than 75% by mass, 80% by mass or more, or 95% by mass or more. By making the zirconium oxide content 65% by mass or more, in addition to improving mechanical strengths such as three-point bending strength and fracture toughness, the hardness can also be reduced, thereby improving processability. The zirconium oxide content of the sintered body is 100% by mass or less; in a sintered body containing only zirconium oxide containing a stabilizing element, the zirconium oxide content is 100% by mass. The zirconium oxide content can be calculated as the ratio of the total mass of zirconium oxide and the stabilizing element converted to oxide to the mass of the sintered body converted to oxide.
[0045] The sintered body of the present embodiment may contain unavoidable impurities such as hafnium oxide (HfO2), but preferably does not contain any substance other than stabilizing elements, zirconium oxide, aluminum oxide, dispersed phase, coloring components as required, and unavoidable impurities. In the present embodiment, the calculation of the values related to the composition, such as the content of each component of the sintered body, can be performed by treating hafnium oxide as zirconium oxide (ZrO2).
[0046] For example, in the case where the sintered body of the present embodiment is a sintered body containing a composite oxide represented by ABO3 or AB2O4, lanthanum hexaaluminate and aluminum oxide as coloring components, and zirconium oxide containing gadolinium and yttrium as stabilizing elements, the content of each component can be calculated as follows. In the following formula, the mass of HfO2 is assumed to be included in the term of ZrO2.
[0047] Coloring component amount [mass %] = {(ABO3 + AB2O4) / (Gd2O3 + Y2O3 + ZrO2 + La2O3 + Al2O3
[0048] +ABO3+AB2O4)}×100
[0049] Aluminum content [mass %] = {Al2O3 / (Gd2O3+Y2O3+ZrO2+La2O3+Al2O3+ABO3+AB2O4)}
[0050] ×100
[0051] Lanthanum content [mass %] = {La2O3 / (Gd2O3+Y2O3+ZrO2+La2O3+Al2O3+ABO3+AB2O4)}
[0052] ×100
[0053] Stabilizing element content [mol%] = {(Gd2O3+Y2O3) / (Gd2O3+Y2O3+ZrO2)}×100
[0054] Gadolinium amount [mol%]={(Gd2O3) / (Gd2O3+Y2O3+ZrO2)}×100
[0055] Amount of yttrium [mol%]={(Y2O3) / (Gd2O3+Y2O3+ZrO2)}×100
[0056] The sintered body of the present embodiment has a peak at 2θ=34.0°±0.2° in the XRD spectrum. The XRD spectrum can be measured by a conventional crystal analysis X-ray diffraction device (for example, device name: X'pert PRO MPD, manufactured by Spectris Corporation).
[0057] The following conditions can be mentioned as measurement conditions.
[0058] Radiation source: Cu Kα radiation
[0059] Tube voltage: 40kV
[0060] Tube current: 40mA
[0061] Scanning speed: 4° / min
[0062] Step size: 0.02°
[0063] Measuring angle: 27~37°
[0064] After measuring under the above measurement conditions, analysis can be performed using the X-ray analysis software "SmartLab Studio II".
[0065] The following conditions can be mentioned as analysis conditions (peak shape fitting conditions).
[0066] Peak shape: Split-type pseudo-Voigt function
[0067] Background type: B-spline
[0068] From the above analysis results, the angle and intensity of the peak top can be confirmed in the XRD spectrum.
[0069] The ratio of the intensity of 2θ=30.0°±0.2° to the intensity of the peak top of 2θ=34.0°±0.2° in the XRD spectrum (hereinafter also referred to as "XRD peak intensity ratio") refers to the value obtained by dividing the intensity of the peak of 2θ=30.0°±0.2° by the intensity of the peak of 2θ=34.0°±0.2°, with reference to the angle and height of the peak top obtained from the above analysis results. From the viewpoint of processability, the XRD peak intensity ratio is preferably 1000 or less, 800 or less, or 500 or less. In addition, from the viewpoint of light-shielding properties, the XRD peak intensity ratio is preferably 10 or more, 15 or more, or 20 or more. The XRD peak intensity ratio is preferably 10 or more and 1000 or less, 15 or more and 800 or less, or 20 or more and 500 or less. Thereby, a sintered body having both light-shielding properties and processability can be obtained.
[0070] The density of the sintered body of this embodiment is preferably high. That is, the measured density of the sintered body of this embodiment is preferably 5.4 g / cm 3 More preferably, 5.5 g / cm 3 Above or 5.6g / cm 3 The measured density of the sintered body of this embodiment can be 6.3 g / cm 3 Below or 6.2g / cm 3The measured density is preferably 5.4 g / cm 3 Above and 6.3g / cm 3 Below, 5.5g / cm 3 Above and 6.2g / cm 3 Below, or 5.6g / cm 3 Above and 6.2g / cm 3 the following.
[0071] In the present embodiment, the measured density is a value obtained as a ratio of a mass obtained by mass measurement to a volume obtained by a method in accordance with JISR 1634 (so-called Archimedean method).
[0072] The crystal phase of zirconium oxide in the sintered body of the present embodiment preferably includes at least tetragonal crystals, and may include tetragonal crystals and at least one selected from cubic crystals and monoclinic crystals.
[0073] The shape of the sintered body of the present embodiment may be at least one selected from the group consisting of spherical, substantially spherical, elliptical, disc-shaped, cylindrical, cubic, rectangular, polyhedral, and substantially polyhedral shapes, and any shape may be used to achieve a desired purpose such as various uses.
[0074] The Vickers hardness (Hv) of the sintered body of the present embodiment is preferably below 12.3GPa or below 12GPa. Thus, the processability suitable for various purposes is improved. Specifically, grindability and cutting properties are improved, and in addition, defects, i.e. cracks, notches, etc. caused by processing are not easy to occur. In order to make the sintered body surface difficult to cause damage, for example, preferably more than 9GPa, more preferably more than 10GPa, and further preferably more than 11GPa. The Vickers hardness is preferably more than 9GPa and less than 12.3GPa, more than 10GPa and less than 12GPa, or more than 11GPa and less than 12GPa.
[0075] In the present embodiment, the Vickers hardness can be measured by a method in accordance with JIS R1610: 2003. As measurement conditions of the Vickers hardness, the following conditions can be exemplified.
[0076] Test sample: (sample thickness) 1.5 ± 0.5 mm
[0077] (Measurement of surface roughness) Ra≤0.02μm
[0078] Measuring load: 10kgf
[0079] The determination can be carried out using a conventional Vickers testing machine (e.g., Q30A, manufactured by Verder Scientific) with a diamond regular quadrangular pyramid indenter. During the determination, the indenter is statically pressed into the surface of the test sample to form an indentation mark formed on the surface of the test sample, and the diagonal length of the indentation mark is measured visually. Using the obtained diagonal length, the Vickers hardness can be obtained by the following formula.
[0080] Hv=F / {d 2 / 2sin(α / 2)}
[0081] In the above formula, Hv is the Vickers hardness (GPa), F is the measuring load (10 kgf), d is the diagonal length of the indentation mark (mm), and α is the angle between the opposing faces of the indenter (136°).
[0082] In the present embodiment, the total light transmittance is preferably less than 20%, more preferably less than 15%. Thus, when used for various purposes, it is not easily affected by the color tone of the substrate, etc. The so-called total light transmittance refers to the total light transmittance (the sum of the linear transmittance and the diffuse transmittance) when the thickness of the sintered body is set to 1±0.05mm, the two sides are mirror-polished so that the surface roughness Ra≤0.02μm, and D65 is used as the light source. If the total light transmittance is low, a sintered body with high light-shielding properties can be obtained. The total light transmittance of the sintered body of the present embodiment can be exemplified as more than 1%, and further more than 3%. The total light transmittance is preferably more than 1% and less than 20%, or more than 3% and less than 15%.
[0083] As an index of the fracture resistance of the sintered body in the present embodiment, the fracture toughness value can be exemplified. The fracture toughness value is a value of fracture toughness (MPa·m 0.5 ). It should be noted that JIS R1607 stipulates two methods for measuring fracture toughness: the IF method and the SEPB method. The IF method is a simple measurement method, but the measured value tends to be larger than that of the SEPB method.
[0084] The fracture toughness value of the sintered body of the present embodiment by the IF method is 10 MPa·m 0.5 Above or 11MPa·m 0.5 Above, another example is 16MPa·m 0.5 Below or 15MPa·m 0.5 Below. The total light transmittance can be 10MPa·m 0.5 Above and 16MPa·m 0.5 Below, or 11MPa·m 0.5 Above and 15MPa·m 0.5 the following.
[0085] The sintered body of this embodiment preferably includes zirconium oxide grains and dispersed phase grains, and the average grain size of the zirconium oxide grains is preferably smaller than the average grain size of the dispersed phase grains. This makes it difficult for the dispersed phase grains to aggregate, improves the mechanical strength, and easily reduces the total light transmittance.
[0086] The average grain size of the zirconium oxide crystal grains is preferably 100 nm to 500 nm, or 200 nm to 400 nm.
[0087] The average grain size of the dispersed phase grains is preferably 100 nm to 800 nm, or 200 nm to 700 nm.
[0088] The average grain size of zirconium oxide grains and dispersed phase grains is an average diameter based on the number of grains constituting the sintered body, and is determined by image analysis of a scanning electron microscope (hereinafter also referred to as "SEM") observation image obtained by heat treating the mirror-polished sintered body.
[0089] SEM observation can be performed using a conventional scanning electron microscope (e.g., JSM-IT 500LA, manufactured by JEOL Ltd.). The SEM observation can be performed by appropriately setting the observation magnification in such a way that the number of grains (grains observed without grain boundary interruption in the SEM observation diagram (described later)) for image analysis reaches 150 ± 50. In order to suppress the difference in the observed grains caused by the difference in the SEM observation site, it is preferred to obtain the SEM observation diagram in such a way that the total of the grains observed by 2 or more, preferably 3 or more and 5 or less SEM observation diagrams reaches the above-mentioned number of grains. As conditions for SEM observation, the following conditions can be exemplified.
[0090] Accelerating voltage: 5kV~15kV
[0091] Observation magnification: 5000 times to 40000 times
[0092] The image analysis of the SEM observation image can be performed using image analysis software (e.g., Mac-View Ver.5, manufactured by MOUNTECH Co., Ltd.). Specifically, the crystal grains observed without grain boundary interruption in the SEM observation image are extracted, and the area [nm] of each extracted crystal grain is calculated. 2 ]. The diameter [nm] of a circle having an area equal to the obtained area is converted, and the obtained diameter (Heywood diameter; hereinafter also referred to as "equivalent circle diameter") is regarded as the grain size of the crystal grains. The average value of the equivalent circle diameters of the extracted crystal grains is regarded as the average grain size of the sintered body.
[0093] In addition, since it is difficult to observe the contrast of the grain boundaries in the sintered body after mirror polishing, it is necessary to perform the heat treatment within a range in which the grain size does not change.
[0094] Conditions for heat treatment of the sintered body include, for example, holding the sintered body at a temperature 50° C. or higher lower than the sintering temperature for 0.1 hour or longer. Examples of the conditions are as follows.
[0095] Heat treatment temperature: 1100°C or higher and 1500°C or lower
[0096] Heat treatment time: 0.1 hour or more and 1.0 hour or less
[0097] It should be noted that in a sintered body containing a pigment component, aluminum oxide, and hexaaluminate, and in which the pigment component, aluminum oxide, and hexaaluminate are precipitated as crystal grains, in addition to zirconium oxide crystal grains, the SEM observation image also contains crystal grains of the pigment component, crystal grains of aluminum oxide, and crystal grains of the dispersed phase. In this case, the crystal grains of the pigment component, the crystal grains of aluminum oxide, and the crystal grains of the dispersed phase can be observed to have a black hue compared to the crystal grains of zirconium oxide, and can also be detected by SEM-EDS, so that the crystal grains of zirconium oxide and the crystal grains of the dispersed phase can be distinguished, and the average grain size of each can be calculated. In the case where the sintered body contains both crystal grains of hexaaluminate and crystal grains of aluminate, these two are regarded as crystal grains of the dispersed phase, and the average grain size is calculated.
[0098] The average aspect ratio of the dispersed phase grains is preferably 1.5 or more, 1.8 or more, 1.9 or more, or 2.0 or more, preferably 3.5 or less, 3.0 or less, or 2.8 or less. If the average aspect ratio is 1.5 or more, the dispersed phase grains block cracks and are difficult to expand, so the fracture toughness is easily improved. If the average aspect ratio is 3.5 or less, the dispersed phase grains are not easy to aggregate, and the bending strength is not easy to reduce. The average aspect ratio is more preferably 1.5 or more and 3.5 or less, 1.8 or more and 3.0 or less.
[0099] The aspect ratio of dispersed phase grains is determined as follows: dispersed phase grains are extracted in the same manner as the above-mentioned determination of the average grain size, and the values of the major axis / minor axis of these grains when they are approximated as ellipses are calculated, and the average of these values is determined as the average aspect ratio.
[0100] The color tone of the sintered body of the present embodiment is arbitrary, but in the case of a sintered body containing no coloring component, the color tone of the sintered body can be exemplified by CIE1976 (L * a * b * ) Lightness L in color space * It is 70 or more, 75 or more, or 80 or more. * The upper limit of L is 100. That is, the lightness L* Examples include 70 to 100, 75 to 100, or 80 to 100.
[0101] In this case, the chroma a * and b * They can be exemplified as -3≤a * ≤1 and -2≤b * ≤5.
[0102] Lightness L * 、Color a * and b * The lightness L can be measured by a method in accordance with JIS Z 8722 using a conventional spectrophotometer (for example, CM-700d, manufactured by Konica Minolta Inc.). * The measurement conditions include the following conditions. The measurement is preferably a measurement using a black plate as a background (so-called black background measurement).
[0103] Light source: D-65 light source
[0104] Viewing angle: 10°
[0105] Measurement method: SCI
[0106] As the measurement sample, a disk-shaped sintered body with a diameter of 20 mm and a thickness of 2.7 mm is used, and the surface to be evaluated is mirror-polished (Ra ≤ 0.02 μm), and the color tone is evaluated. In addition, as an effective area for color tone evaluation, a diameter of 10 mm is given.
[0107] On the other hand, when the sintered body of the present embodiment contains a coloring component, the lightness L * is greater than 0 and less than 95, chroma a * is greater than -5 and less than 15, and the chroma b * It is above -30 and below 40.
[0108] The sintered body of this embodiment can be applied to existing sintered body applications, particularly to the applications of zirconia sintered bodies such as structural materials, optical materials, and dental materials. It can also be used as a cover material for accessories of ornaments, watches, casings, etc., and as an exterior component of portable electronic devices such as mobile phones, which require higher light-shielding properties.
[0109] Hereinafter, a method for producing a sintered body according to the present embodiment will be described.
[0110] The method for producing the sintered body of the present embodiment is not particularly limited, and the sintered body of the present embodiment can be obtained by a method having a step of sintering a mixed powder containing at least zirconium oxide powder, a stabilizing element source, an aluminum oxide source, and a dispersed phase source (hereinafter also referred to as a "sintering step"). When the mixed powder is sintered to produce the sintered body, the powder can be molded into a molded body (powder compact) before sintering.
[0111] The molded body contains zirconium oxide, a stabilizing element source, an aluminum oxide source, and a dispersed phase source.
[0112] The stabilizing element source may be at least one of a compound containing the stabilizing element and a precursor of the compound containing the stabilizing element. The compound containing the stabilizing element is preferably at least one selected from the group consisting of chlorides, sulfides, nitrates, hydroxides, or oxides of the stabilizing element. The content of the stabilizing element source in the molded body may be equal to the amount of the stabilizing element in the target sintered body.
[0113] The alumina source is at least any one of alumina (Al2O3) and a compound containing aluminum (Al) as its precursor, and may include one or more selected from the group consisting of aluminates, hexaaluminates, aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum hydroxide and aluminum oxide, preferably one or more selected from the group consisting of aluminates, hexaaluminates and aluminum oxide.
[0114] When zirconium oxide containing a stabilizing element is used as zirconium oxide, any method for making zirconium oxide contain the stabilizing element is used. For example, the following method can be used: a hydrated zirconium oxide sol is mixed with a stabilizing element source having the same content as the target stabilizing element, and then dried, pre-calcined, and washed with water.
[0115] The molded body may contain a coloring component source (pigment) as required. The content of the coloring component source in the molded body is as long as it is equal to the content of the coloring component of the target sintered body. For example, a molded body containing the coloring component source can be obtained by preparing a mixed powder mixed with the above-mentioned powder and the coloring component source.
[0116] The mixing method of the powder and the coloring component source is arbitrary, preferably at least one of dry mixing and wet mixing, more preferably wet mixing, and further preferably wet mixing using a ball mill. Examples of dispersed phase sources include at least one of hexaaluminate powder and a precursor of hexaaluminate. A sintered body containing hexaaluminate can be obtained by a manufacturing method in which a hexaaluminate powder or a powder of a precursor thereof is mixed with zirconium oxide powder and sintered. Specifically, examples include: a method in which a powder of a hexaaluminate precursor is sintered to obtain a hexaaluminate powder, and then the powder is mixed with zirconium oxide powder and sintered; and a method in which a powder of a hexaaluminate precursor is mixed with zirconium oxide powder and sintered.
[0117] Examples of the precursor of the hexaaluminate include metal oxides (RO, R2O3, or mixtures thereof containing a metal element R and an oxygen atom O), and at least one of aluminum oxide and aluminate, preferably metal oxides and aluminum oxide.
[0118] Examples of the metal oxide contained in the precursor of the hexaaluminate include one or more selected from the group consisting of magnesium oxide (MgO), calcium oxide (CaO), strontium oxide (SrO), barium oxide (BaO), lanthanum oxide (La2O3), neodymium oxide (Nd2O3) and samarium oxide (Sm2O3). Examples of the aluminate include one or more selected from the group consisting of MgAl2O4, CaAl2O4, SrAl2O4, BaAl2O4, LaAlO3, NdAlO3 and SmAlO3.
[0119] As a method for preparing aluminate, it is preferred that the metal oxide and alumina are mixed in a manner such that the metal R and Al reach R:Al=1:1 in terms of molar conversion, the mixed powder is placed in an alumina crucible, and sintered at 1100°C to 1250°C for 2 hours to 4 hours. As a method for preparing hexaaluminate, it is preferred that the metal oxide and alumina are mixed in a manner such that the metal R and Al reach R:Al=1:6 in terms of molar conversion, the mixed powder is placed in an alumina crucible, and sintered at 1400°C to 1500°C for 4 hours to 8 hours.
[0120] The molding method may be any known molding method that can make the mixed powder into a pressed powder body. It is preferably at least one selected from uniaxial press molding, isostatic pressing, injection molding, extrusion molding, tumble granulation and casting molding, more preferably at least any one of uniaxial press molding and isostatic pressing, further preferably at least any one of cold isostatic pressing and uniaxial press molding (powder pressing), and more preferably a method of performing cold isostatic pressing after uniaxial press molding.
[0121] In the sintering step, the mixed powder, preferably the molded body, is sintered to obtain a sintered body. The sintering method is arbitrary, and known sintering methods such as normal pressure sintering, pressure sintering, and vacuum sintering can be exemplified. As a preferred sintering method, normal pressure sintering can be cited, and the sintering method is preferably only normal pressure sintering. Thus, the sintered body of the present embodiment can be obtained as a so-called normal pressure sintered body. Normal pressure sintering refers to a method in which no external force is applied to the sintered object (powder, molded body or pre-sintered body) during sintering, and sintering is performed only by heating.
[0122] Regarding the conditions for normal pressure sintering, the sintering temperature is preferably 1100° C. to 1600° C., 1200° C. to 1580° C., or 1200° C. to 1560° C., and examples thereof include 1200° C. to 1500° C. or 1200° C. to 1450° C. In addition, as the sintering atmosphere, at least one of an air atmosphere and an oxygen atmosphere can be cited, and an air atmosphere is preferred.
[0123] The sintering time may be appropriately adjusted depending on the sintering method, the size and amount of the powder (molded body) to be sintered, and the type and performance of the sintering furnace used, and may be, for example, 0.5 hours to 8 hours.
[0124] Above, embodiments of the present invention have been described, but the present invention is not limited by these embodiments. For example, the numerical range of any combination of the upper limit and lower limit specifically described in the present embodiment is also included in the present invention. In addition, the numerical range obtained by replacing at least any one of the upper limit and lower limit with the value of the following embodiment is also included in the present invention.
[0125] Example
[0126] Hereinafter, the present embodiment will be specifically described by way of examples, but the present embodiment is not limited to these examples.
[0127] (Powder X-ray diffraction measurement)
[0128] The sintered bodies of Examples and Comparative Examples were subjected to X-ray diffraction measurement under the following conditions, and the obtained XRD patterns were analyzed using the X-ray analysis software "SmartLab Studio II".
[0129] The sintered body sample used was a disk-shaped sample with a diameter of 20 mm and a thickness of 1.7 mm. The surface of the sintered body sample was mirror-polished to a surface roughness Ra ≤ 0.02 μm, and used as a measurement surface.
[0130] The measurement conditions were set to the following conditions.
[0131] Radiation source: Cu Kα radiation
[0132] Tube voltage: 40kV
[0133] Tube current: 40mA
[0134] Scanning speed: 4° / min
[0135] Step size: 0.02°
[0136] Measuring angle: 27~37°
[0137] The analysis conditions (peak shape fitting conditions) are as follows.
[0138] Peak shape: Split-type pseudo-Voigt function
[0139] Background type: B-spline
[0140] (Vickers hardness)
[0141] The Vickers hardness was measured using a conventional Vickers testing machine (device name: Q30A, manufactured by Verder Scientific) having an indenter of a regular quadrangular pyramid made of diamond. The Vickers hardness was measured under the following conditions.
[0142] Test sample: (sample thickness) 1.5 ± 0.5 mm
[0143] (Measurement of surface roughness) Ra≤0.02μm
[0144] Measuring load: 10kgf
[0145] The indenter is statically pressed into the surface of the measurement sample, and the diagonal length of the indentation mark formed on the surface of the measurement sample is visually measured. The obtained diagonal length is used to calculate the Vickers hardness from the following formula.
[0146] Hv=F / {d 2 / 2sin(α / 2)}
[0147] (density)
[0148] The measured density of the sintered body sample was calculated as the ratio (g / cm2) of the volume measured by the Archimedean method based on JIS R1634 to the mass measured by mass measurement. 3 Before the measurement, the mass of the dried sintered body was measured, and then the sintered body was placed in water and boiled for 1 hour as a pretreatment.
[0149] (Total light transmittance)
[0150] The total light transmittance of the sintered body sample was measured according to the method of JIS K 7361-1. The measurement was performed using a conventional haze meter (device name: NDH4000, manufactured by Nippon Denshoku Co., Ltd.) equipped with a D65 light source. The sintered body sample had a thickness of 1 mm ± 0.05 mm and a diameter of 20 mm, and both sides were mirror-polished to a surface roughness Ra ≤ 0.02 μm.
[0151] (Average grain size)
[0152] For the sample after the mirror-polished sintered body was thermally etched, the average grain size was obtained by the above method using SEM-EDS (device name: JSM-IT500LA, manufactured by JEOL Ltd.) and image analysis software (software name: Mac-View Ver.5, manufactured by MOUNTECH Co., Ltd.). It should be noted that the thermal etching was performed for 0.5 hours at a value 100°C lower than the sintering temperature of the sintered body. Using a SEM vapor deposition device (DII-29010SCTR SmartCoater, manufactured by JEOL Ltd.), the sample after thermal etching was coated with Au and then observed by SEM.
[0153] About the average grain size of zirconium oxide grains, for the SEM observation diagram imported into the image analysis software, the grain boundaries of zirconium oxide grains are tracked on the software, thereby extracting grains with no interruption in the grain boundaries. After extraction, the area and equivalent circular diameter of the grains are obtained using the image analysis software, and the average grain size is obtained. It should be noted that in a sintered body containing pigment components, aluminum oxide, hexaaluminate, and pigment components, aluminum oxide, and dispersed phases are precipitated as grains, in addition to the grains of zirconium oxide, the grains of the pigment components, the grains of aluminum oxide, and the grains of dispersed phase are also included in the SEM observation diagram. In this case, the grains of the pigment components, the grains of aluminum oxide, and the grains of the dispersed phase can be observed as having a black hue compared to the grains of zirconium oxide, and can also be detected by SEM-EDS, so such grains are excluded, and after extracting 150±50 grains, the area and equivalent circular diameter of the grains are obtained, and the average grain size is obtained.
[0154] The average grain size of the dispersed phase grains was measured in the same manner as the average grain size of the zirconium oxide grains. That is, by tracking the grain boundaries of the dispersed phase grains on the software, the grains with no interruptions in the grain boundaries were extracted. After the dispersed phase grains were extracted by SEM-EDS detection, the area and equivalent circle diameter of the grains were calculated using the image analysis software to calculate the average grain size. 150±50 grains were extracted.
[0155] (Average aspect ratio)
[0156] The average aspect ratio of dispersed phase grains is calculated as follows: That is, for all dispersed phase grains extracted in the measurement of the average grain size, the values of the major axis / minor axis when each of them is approximated as an ellipse are calculated, and the average of these values is obtained as the average aspect ratio.
[0157] (pigment)
[0158] In Example 4, the following pigments were used as pigments containing a coloring component.
[0159] Pigment 1: CoAl2O4 (NF-2800, Nikken Co., Ltd.)
[0160] Pigment 2: Fe2O3 (Iron oxide (III) grade 1, Kanto Chemical Co., Ltd.)
[0161] Pigment 3: ZnO (zinc oxide, special grade, Kishida Chemical Co., Ltd.)
[0162] Synthesis Example 1 (Strontium Hexaaluminate)
[0163] In Example 5, strontium hexaaluminate prepared according to the following procedure was used.
[0164] Strontium oxide (manufactured by Kishida Chemical Co., Ltd.) and alumina (AKP30, manufactured by Sumitomo Chemical Co., Ltd.) were mixed in a molar ratio of Sr:Al=1:6, added to pure water to prepare a slurry, and pulverized and mixed for 24 hours using a ball mill with a zirconia ball of 10 mm in diameter as a pulverizing medium. The pulverized slurry was dried at 110°C in an air atmosphere, and aggregates with an aggregate diameter exceeding 180 μm were removed by sieving to obtain a mixed powder. The mixed powder was heated at 1450°C in an alumina crucible for 6 hours to obtain the strontium hexaaluminate powder used in Example 5.
[0165] Synthesis example 2 (lanthanum aluminate)
[0166] In Example 6, lanthanum aluminate produced according to the following procedure was used.
[0167] After treating lanthanum oxide (manufactured by Yttrium Corporation of Japan) at 700°C in an air atmosphere, the lanthanum oxide and aluminum oxide (AKP30 manufactured by Sumitomo Chemical Co., Ltd.) were mixed in a molar ratio of La:Al=1:1 to obtain a mixed powder. The obtained mixed powder was heat treated at 1450°C in an air atmosphere for 2 hours and then cooled to room temperature. After cooling, the mixture was pulverized and mixed, and heated at 1450°C in an air atmosphere for 2 hours to obtain the lanthanum aluminate powder used in Example 6.
[0168] Synthesis Example 3 (Calcium Hexaaluminate)
[0169] In Examples 8, 9, 10 and Comparative Examples 4 and 5, calcium hexaaluminate produced according to the following procedure was used.
[0170] Calcium oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and aluminum oxide (AKP30 manufactured by Sumitomo Chemical Co., Ltd.) were mixed in a molar ratio of Ca:Al=1:6, added to pure water to prepare a slurry, and pulverized and mixed for 24 hours using a ball mill with a zirconia ball of 10 mm in diameter as a pulverizing medium. The pulverized slurry was dried at 110°C in an air atmosphere, and aggregates with an aggregate diameter of more than 180 μm were removed by sieving to obtain a mixed powder. The mixed powder was heated at 1450°C in an alumina crucible for 6 hours to obtain the calcium hexaaluminate powder used in Example 8.
[0171] Example 1
[0172] The zirconium oxychloride aqueous solution is subjected to a hydrolysis reaction to obtain a hydrated zirconium oxide sol. Gadolinium chloride and yttrium chloride are added to the hydrated zirconium and mixed in such a manner that the gadolinium concentration is 1.4 mol% and the yttrium concentration is 0.4 mol%. After mixing, the mixture is dried in an air atmosphere, and then pre-calcined at 1150° C. for 2 hours in an air atmosphere to obtain a gadolinium-yttrium-stabilized zirconium oxide pre-calcined powder. The obtained pre-calcined powder is washed with pure water and dried to obtain a zirconium oxide powder composed of a gadolinium-yttrium-stabilized zirconium oxide having a gadolinium content of 1.4 mol% and a yttrium content of 0.4 mol%.
[0173] The obtained zirconium oxide powder, strontium oxide powder (manufactured by Kishida Chemical Co., Ltd.) and aluminum oxide (AKP30 manufactured by Sumitomo Chemical Co., Ltd.) were mixed so that the strontium oxide content was 1.45 mass% and the aluminum oxide content was 8.55 mass% to obtain a mixed powder. The mixed powder was added to pure water to prepare a slurry, and the mixture was pulverized and mixed for 48 hours using a ball mill using zirconium oxide balls with a diameter of 10 mm as a pulverizing medium. The pulverized slurry was dried at 110° C. in an air atmosphere, and then coarse particles with an aggregate diameter exceeding 180 μm were removed by sieving, thereby obtaining a mixed powder of this embodiment composed of gadolinium-yttrium-stabilized zirconium oxide containing strontium oxide and aluminum oxide, in which the strontium content was 1.45 mass%, the aluminum oxide content was 8.55 mass%, the gadolinium content was 1.4 mol% and the yttrium content was 0.4 mol%.
[0174] The obtained mixed powder was subjected to a mold pressing process at a pressure of 50 MPa and a cold isostatic pressing (CIP) process at a pressure of 196 MPa to obtain a molded body. The obtained molded body was subjected to normal pressure sintering at a sintering temperature of 1450° C. in an air atmosphere for 2 hours to obtain a sintered body of this embodiment composed of gadolinium-yttrium-stabilized zirconia containing strontium hexaaluminate, in which the strontium content was 1.45 mass%, the aluminum content was 8.55 mass%, the gadolinium content was 1.4 mol%, and the yttrium content was 0.4 mol%. The Vickers hardness of the obtained sintered body was 11.6 GPa, and the total light transmittance was 7%.
[0175] Example 2
[0176] A sintered body of this embodiment consisting of gadolinium-yttrium-stabilized zirconia containing strontium hexaaluminate was obtained by the same method as in Example 1, except that a mixed powder was prepared by using zirconium oxide powder, strontium oxide powder and aluminum oxide powder so that the strontium oxide content was 0.724 mass % and the aluminum oxide content was 4.28 mass %. The sintered body had a strontium content of 0.724 mass %, an aluminum content of 4.28 mass %, a gadolinium content of 1.4 mol % and a yttrium content of 0.4 mol %. The Vickers hardness of the obtained sintered body was 11.3 GPa, and the total light transmittance was 15%.
[0177] Example 3
[0178] A sintered body of this embodiment consisting of gadolinium-yttrium-stabilized zirconia containing strontium hexaaluminate was obtained by the same method as in Example 1, except that a mixed powder was prepared from zirconium oxide powder, strontium oxide powder and aluminum oxide powder so that the strontium oxide content was 2.17 mass % and the aluminum oxide content was 12.8 mass %, and the mixed powder was sintered. The sintered body had a strontium content of 2.17 mass %, an aluminum content of 12.8 mass %, a gadolinium content of 1.4 mol % and a yttrium content of 0.4 mol %. The Vickers hardness of the obtained sintered body was 11.7 GPa, and the total light transmittance was 4%.
[0179] Example 4
[0180] A mixed powder was prepared by mixing zirconium oxide powder, strontium oxide powder, aluminum oxide powder and coloring components 1 to 3 so that the strontium oxide content was 1.45 mass%, the aluminum oxide content was 8.55 mass%, the CoAl2O4 content was 0.0100 mass%, the Fe2O3 content was 0.0200 mass%, and the ZnO content was 0.0125 mass%. A sintered body of this example consisting of gadolinium-yttrium-stabilized zirconia containing strontium hexaaluminate, cobalt aluminate, iron oxide and zinc oxide was obtained by the same method as in Example 1, wherein the strontium content was 1.45 mass%, the aluminum content was 8.55 mass%, the CoAl2O4 content was 0.0100 mass%, the Fe2O3 content was 0.0200 mass%, the ZnO content was 0.0125 mass%, the gadolinium content was 1.4 mol% and the yttrium content was 0.4 mol%. The obtained sintered body had a Vickers hardness of 11.6 GPa and a total light transmittance of 2%.
[0181] Example 5
[0182] A sintered body of this embodiment composed of gadolinium-yttrium-stabilized zirconia was obtained by the same method as in Example 1, except that the zirconium oxide powder and the strontium hexaaluminate powder of Synthesis Example 1 were mixed to obtain a strontium hexaaluminate content of 5.00 mass%, a gadolinium content of 1.4 mol%, and a yttrium content of 0.4 mol%. The Vickers hardness of the obtained sintered body was 11.5 GPa, and the total light transmittance was 9%.
[0183] Example 6
[0184] A mixed powder was prepared by using zirconium oxide powder, the lanthanum aluminate powder of Synthesis Example 2 and aluminum oxide powder so that the lanthanum aluminate content was 2.96 mass % and the aluminum oxide content was 7.04 mass %, and the sintering temperature was set to 1400° C., and a sintered body of this example consisting of gadolinium-yttrium-stabilized zirconia containing lanthanum hexaaluminate was obtained by the same method as in Example 1, in which the lanthanum content was 2.25 mass %, the aluminum content was 7.75 mass %, the gadolinium content was 1.4 mol % and the yttrium content was 0.4 mol %. The Vickers hardness of the obtained sintered body was 12.2 GPa, and the total light transmittance was 8%.
[0185] Example 7
[0186] A mixed powder was prepared by mixing zirconium oxide powder, calcium oxide powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and aluminum oxide so that the calcium oxide content was 0.840 mass % and the aluminum oxide content was 9.16 mass %, and the mixed powder was sintered, and the sintering temperature was 1400° C., and a sintered body of this example consisting of gadolinium-yttrium-stabilized zirconium oxide containing calcium hexaaluminate was obtained by the same method as in Example 1, in which the calcium content was 0.840 mass %, the aluminum content was 9.16 mass %, the gadolinium content was 1.4 mol % and the yttrium content was 0.4 mol %. The Vickers hardness of the obtained sintered body was 11.5 GPa, and the total light transmittance was 6%.
[0187] Example 8
[0188] The zirconium oxide powder and the calcium hexaaluminate powder of Synthesis Example 3 were mixed to prepare a mixed powder so that the calcium hexaaluminate content was 10.0 mass %, and the mixed powder was sintered, and the sintering temperature was set to 1400° C., and a sintered body of this example composed of gadolinium-yttrium-stabilized zirconium oxide was obtained by the same method as in Example 1, in which the calcium hexaaluminate content was 10.0 mass %, the gadolinium content was 1.4 mol % and the yttrium content was 0.4 mol %. The Vickers hardness of the obtained sintered body was 11.9 GPa, and the total light transmittance was 6%.
[0189] Example 9
[0190] A sintered body of this example composed of gadolinium-yttrium-stabilized zirconium oxide was obtained by the same method as in Example 1, except that gadolinium oxide was added and mixed to hydrated zirconium so that the gadolinium concentration was 1.6 mol%, the zirconium oxide powder and the calcium hexaaluminate powder of Synthesis Example 3 were mixed so that the calcium hexaaluminate content was 10.0 mass%, and the sintering temperature was 1350° C. The sintered body had a Vickers hardness of 11.3 GPa and a total light transmittance of 14%.
[0191] Example 10
[0192] Gadolinium oxide and yttrium oxide were added and mixed to hydrated zirconium so that the gadolinium concentration was 1.7 mol% and the yttrium concentration was 1.1 mol%, respectively, and the zirconium oxide powder obtained was mixed with the calcium hexaaluminate powder of Synthesis Example 3 so that the calcium hexaaluminate content was 15.0 mass %, and a sintered body of this example composed of gadolinium-yttrium stabilized zirconium oxide was obtained by the same method as Example 1, except that the mixed powder was prepared by adding gadolinium oxide and yttrium oxide to the hydrated zirconium powder so that the calcium hexaaluminate content was 15.0 mass %, the calcium hexaaluminate content was 1.7 mol %, and the yttrium content was 1.1 mol %. The Vickers hardness of the obtained sintered body was 10.7 GPa, and the total light transmittance was 4%.
[0193] Embodiment 11
[0194] Yttrium oxide was added and mixed with hydrated zirconium so that the yttrium concentration was 1.5 mol%, and the obtained zirconium oxide powder was mixed with the strontium hexaaluminate powder of Synthesis Example 1 so that the strontium hexaaluminate content was 5.0 mass % to prepare a mixed powder, and the sintering temperature was set to 1400° C., and a sintered body of this example composed of yttrium-stabilized zirconium oxide was obtained by the same method as Example 1, in which the strontium hexaaluminate content was 5.0 mass % and the yttrium content was 1.5 mol%. The Vickers hardness of the obtained sintered body was 11.5 GPa, and the total light transmittance was 8%.
[0195] Comparative Example 1
[0196] A sintered body of this comparative example composed of gadolinium-yttrium-stabilized zirconia, in which the content of alumina was 10.0 mass%, the content of gadolinium was 1.4 mol%, and the content of yttrium was 0.4 mol%, was obtained by the same method as in Example 1, except that the zirconium oxide powder and the aluminum oxide powder were mixed so that the content of aluminum oxide was 10.0 mass%. The Vickers hardness of the obtained sintered body was 12.4 GPa, and the total light transmittance was 7%.
[0197] Comparative Example 2
[0198] A sintered body of this comparative example composed of gadolinium-yttrium-stabilized zirconia, in which the content of alumina was 10.0 mass % and the content of yttrium was 2.0 mol %, was obtained by the same method as in Example 1, except that yttrium oxide was added and mixed with hydrated zirconium so that the yttrium concentration was 2.0 mol %, and a mixed powder was prepared by mixing zirconium oxide powder and alumina powder so that the content of alumina was 10 mass %. The Vickers hardness of the obtained sintered body was 12.8 GPa, and the total light transmittance was 7%.
[0199] Comparative Example 3
[0200] A sintered body of this comparative example composed of gadolinium-yttrium-stabilized zirconia containing strontium oxide was obtained by the same method as in Example 1, except that gadolinium oxide and yttrium oxide were added and mixed to hydrated zirconium so that the gadolinium concentration was 1.5 mol% and the yttrium concentration was 0.5 mol%, respectively, and a mixed powder was prepared by mixing zirconium oxide powder and strontium oxide powder so that the strontium oxide content was 1.45 mass%. In this sintered body, the strontium content was 1.45 mass%, the gadolinium content was 1.5 mol%, and the yttrium content was 0.5 mol%. The Vickers hardness of the obtained sintered body was 11.0 GPa, and the total light transmittance was 25%.
[0201] Comparative Example 4
[0202] A sintered body composed of gadolinium-stabilized zirconium oxide was obtained by the same method as in Example 1, except that gadolinium oxide was added and mixed to hydrated zirconium so that the gadolinium concentration was 3.5 mol%, and zirconium oxide powder and calcium hexaaluminate were mixed so that the calcium hexaaluminate content was 15.0 mass%, and the gadolinium content was 3.5 mol%. The Vickers hardness of the obtained sintered body was 12.4 GPa, and the total light transmittance was 5%.
[0203] Comparative Example 5
[0204] A sintered body composed of yttrium-stabilized zirconium oxide containing calcium hexaaluminate, wherein the calcium hexaaluminate content was 15.0 mass % and the yttrium content was 3.0 mol %, was obtained by the same method as in Example 1, except that yttrium oxide was added and mixed with hydrated zirconium so that the yttrium concentration was 3.0 mol %, and a mixed powder was prepared by mixing the obtained zirconium oxide powder with calcium hexaaluminate so that the calcium hexaaluminate content was 15.0 mass %, and the yttrium content was 3.0 mol %. The obtained sintered body had a Vickers hardness of 12.5 GPa and a total light transmittance of 4%.
[0205] Table 1 shows the compositions and sintering temperatures of the sintered bodies of these Examples and Comparative Examples, and Table 2 shows the evaluation results.
[0206] [Table 1]
[0207]
[0208] [Table 2]
[0209]
[0210] In Table 1, the "Al content" column indicates the aluminum content, the "Zr particle size" column indicates the average grain size of the zirconium oxide grains, and the "dispersed phase particle size" column indicates the average grain size of the dispersed phase grains. In the "Stabilizing element content" column, the "Additives" column, and the "Al content" column, the case where it is not used as a raw material is indicated as "-". In the "XRD peak intensity ratio" column, when the peak of 34.0°±0.2° is not detected in the XRD analysis, it is recorded as "-". In addition, for Comparative Example 3 that does not contain a dispersed phase, the "Dispersed phase particle size" column and the "Average aspect ratio" column are "-".
[0211] The Vickers hardness of the sintered body of each example is 12.3 GPa or less, and the total light transmittance is 20% or less.
[0212] The sintered body of the embodiment has a lower Vickers hardness and a lower total light transmittance than the sintered body of Comparative Example 1 comprising zirconium oxide and aluminum oxide containing gadolinium and yttrium as stabilizing elements, and the sintered body of Comparative Example 2 comprising zirconium oxide and aluminum oxide containing only yttrium as a stabilizing element. That is, the processability is high and the light-shielding property is also high. In addition, the sintered body of the embodiment has a lower Vickers hardness and a lower total light transmittance than the sintered body of Comparative Example 3 comprising zirconium oxide and strontium containing gadolinium and yttrium as stabilizers. In addition, the sintered body of the embodiment has a lower Vickers hardness and also ensures light-shielding property compared to the sintered bodies of Comparative Example 4 with a gadolinium content of 3.5 mol% and Comparative Example 5 with a yttrium content of 3.0 mol%.
[0213] From the above, it was confirmed that the sintered body of this example has high processability and excellent light shielding property.
[0214] It should be noted that this application is based on Japanese Patent Application (Japanese Patent Application No. 2022-158849) filed on September 30, 2022, the entire contents of which are incorporated herein by reference. In addition, all references cited herein are incorporated in their entirety.
Claims
1. A sintered body, characterized in that: The sintered body comprises zirconium oxide containing a stabilizing element, wherein the content of the stabilizing element is less than 3.0 mol %, and the sintered body has a peak at 2θ=34.0°±0.2° in an XRD spectrum.
2. The sintered body according to claim 1, wherein The stabilizing element includes at least one selected from the group consisting of yttrium, gadolinium, ytterbium, and erbium.
3. The sintered body according to claim 1 or 2, wherein The stabilizing element includes yttrium and at least one selected from gadolinium, ytterbium and erbium.
4. The sintered body according to any one of claims 1 to 3, wherein The ratio of the intensity at 2θ=30.0°±0.2° to the intensity at the peak top at 2θ=34.0°±0.2° in the XRD spectrum is 10 or more and 1,000 or less.
5. The sintered body according to any one of claims 1 to 4, wherein The sintered body contains at least one selected from magnesium, calcium, strontium, barium, lanthanum, neodymium, and samarium, and aluminum.
6. The sintered body according to any one of claims 1 to 5, wherein The Vickers hardness of the sintered body is 12.3 GPa or less.
7. The sintered body according to any one of claims 1 to 6, wherein The total light transmittance of the sintered body is less than 20%.
8. The sintered body according to any one of claims 1 to 7, wherein The measured density of the sintered body is 5.4 g / cm 3 Above and 6.3g / cm 3 the following.
9. The sintered body according to any one of claims 1 to 8, wherein The sintered body comprises zirconium oxide grains and dispersed phase grains, wherein the average grain size of the zirconium oxide grains is smaller than the average grain size of the dispersed phase grains.
10. The sintered body according to any one of claims 1 to 9, wherein The sintered body includes dispersed phase grains, and the average aspect ratio of the dispersed phase grains is 1.5 or more and 3.5 or less.
Citation Information
Patent Citations
Machinable zirconia and method for producing the same
JP2015127294A
Cover tape for electronic component packaging, and electronic component package
JP2022158849A